Differences between networks of cognitive emotion regulation strategies in medical students with and without a history of non-suicidal self-injury - Reza Zadehparizi; Amir Sam Kianimoghadam (Journal of Education and Health Promotion)
BACKGROUND: Non-suicidal self-injury (NSSI) is deliberate self-harm without the intent to die. NSSI is associated with mental health issues and has a higher prevalence among medical students. Understanding the cognitive emotion regulation strategies in NSSI is important for intervention and prevention. Network analysis provides a holistic perspective on these strategies. MATERIALS AND METHODS: Participants were 405 individuals (68.6% female) with a mean age of 22.7 years (standard deviation: 3.97, range: 17–55 years), recruited from Tehran, Iran. Upon conducting an initial screening, it was found that 68 individuals from our sample acknowledged a prior history of NSSI. RESULTS: A network analysis showed that that students with a history of NSSI perceived themselves to have difficulties in putting into perspective, positive reappraisal, and self-blame. Compared to students without NSSI, those with NSSI exhibited negative associations between putting into perspective and rumination (PIP__RUM: -0.240) and positive associations between positive refocusing and catastrophizing (PR__Catast: 0.61). CONCLUSIONS: This study discovered notable distinctions in the cognitive processing and coping strategies of medical students with and without a history of NSSI. These findings contribute to the existing literature on the link between cognitive-emotional processes and NSSI, informing the development of interventions to decrease such behaviors.